Pengaruh Disiplin Terhadap Hasil Belajar Sosiologi Siswa di SMA Muhammadiyah Patinia Desa Kawa Kecamatan Seram Barat Kabupaten Seram Bagian Barat - Iwan S. Simatauw; Lambertus J. Lokollo; R. Tutupary (Peneliti.net, 2021)
The purpose of this study was to determine the effect of discipline on Sociology Learning Outcomes of Class XI Students of SMA Muhammadiyah Patinia, Kawa Village, West Seram District, West Seram Regency. This study uses quantitative research, because the data obtained are analyzed according to the statistical methods used and then interpreted. The results of the study show that there is a very significant influence between disciplines on the learning outcomes of Sociology Students of Class XI SMA Muhammadiyah Patinia. This means that the lower the student's discipline, the lower the student's learning outcomes and vice versa if the higher the student's discipline, the higher the student's learning outcomes. However, in general, it can strengthen the learning outcomes of students who get good grades from the test results because students who are not disciplined think that learning is a compulsion.